A FORMALISM APPROACH ON DAPHNE DU MAURIERâS REBECCA - Sulistyorini, Haryati (LITE, 2007)
Literature is a human living description expressed by the authors through their literary texts. Understanding literature is about how to understand the texts that contain their creative process. Formalism is one of the approaches aimed at finding out what and why the motor of the story works in the literary texts. Daphne du Maurierâs was analyzed using the formalism approach. The main character obsession is the one that runs the story, which arouses various conflicts among characters. How the main character solves the problems in the conflict is the final answer of the story analysis using the formalism approach.Keywords: formalism, tension, âIâ character, Rebecca